Fertility management for malignant ovarian germ cell tumors patients. (December 2017) - Di Tucci, Chiara; Casorelli, Assunta; Morrocchi, Elisa; Palaia, Innocenza; Muzii, Ludovico; Panici, Pierluigi Benedetti
Highlights: Fertility management of patients with malignant ovarian germ cell cancer. Patients with malignant ovarian germ cell cancer underwent surgical and/or medical treatment. Tailoring fertility management are need in patients underwent treatment for malignat ovarian germ cell tumor. Abstract: Malignant Germ Cell Tumors have primarily affecting adolescents and young adults. In advanced disease, greater than 70% of patients can be cured with standard chemotherapy regimens and fertility-sparing surgery appears to be safe with excellent survival after long-term follow-up. Due to their rarity, follow up and fertility management is largely based on trials of epithelial ovarian cancer or on few small studies. We report a review of the literature studies about the assessment, the monitoring and the treatment of fertility for Malignant Germ Cell Tumors as pratical guidelines for management of fertility in these patients.